Structural detailing in steel a comparative study of British, European and American codes and practices - Bangash, M. Y. H. (Thomas Telford, 2000)
This extensive manual looks at the various aspects of steel construction. It covers the full scope of structural steelwork detailing, including fundamentals, draughting practice and conventions, conventional methods of detailing components, full scale constructed facilities and computer aided practices. A number of codes have also been included.
Keywords: Building, Iron and steel -- Details.; Building, Iron and steel -- Standards.; Steel, Structural.; elektronické knihy; electronic books